The Influence of Spontaneity Smart Circuit Games on Group A Rough and Social Motor Development of Children in Wiyung District at Surabaya - Indrawati, Sus; Bachri, Bachtiar S.; Mariono, Andi (International Journal for Educational and Vocational Studies, 2020)
This research aims to determine the effect of the "Smart Spontaneity" circuit game on the gross motor and social development of group A children in Wiyung sub-district, Surabaya. This research is based not only on the problems that occur in group A children in Wiyung Subdistrict, Surabaya, it is also based on innovations in learning done in kindergartens. This research uses a quantitative approach and uses a type of experimental research. The population in this study used all students in the two schools included in the Wiyung sub-district, namely AT Taqwa Kindergarten and Taman Ananda Kindergarten with almost the same characteristics. Sampling in this study uses cluster random sampling techniques, so the samples used in this study are students A1 and A2 in At Taqwa Kindergarten and A1 and A2 in Taman Ananda Kindergarten. The techniques and data collection used are Pretest and Posttest which have a function to find out the influence of spontaneous intelligent circuit play on the gross and social motor development of group A children. The results of this study are (1) there is the influence of spontaneity smart circuit play on the gross motor development of group A children in Wiyung Subdistrict, Surabaya, (2) there is an influence of games on the social development of group A children in Wiyung Subdistrict, the results were obtained tcount> ttable with a real level of 5% so that 9.2> 0.5 with the average difference in the experimental class and the control class . The average experimental class was 21.4 and the average control class was 13.2. Based on the results of data analysis, it can be concluded that the circuit game "Smart Spontaneity" affects the gross motor development of children in group A and the game circuit "Smart Spontaneity" affects the social development of children in group A in Wiyung District, Surabaya.